(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The multicomponent method of assessing the progress in physics of students from the Technical University of Gabrovo is discussed in the paper. It is shown that tests papers as a modern form of examining students can successfully be combined with other traditional forms of examination. In that way the teacher can get important feedback on how students understand lectures and laboratory teaching material during the semester and to adjust their work so that they can in time adapt to the necessary level. Thus, students are actively involved in the learning process, which improves the results they show at the final exam. These conclusions are based on the results of the last decade, ever since the method was introduced.